Une étude sélective des mesures de bien-être d’un individu - Laferrière, Richard (L'Actualité économique, 1983)
This paper begins by presenting several well-known measures for a welfare variation of an individual following a change of prices and/or income. Then we discuss the computation of some of these measures and show some procedures which appeared recently in the literature. We also propose an extension of the Hausman's paper. The last section points out the roles of the compensating and equivalent variations. Throughout the paper we use a numerical example for illustrating purposes.